ASSERTIVE BEHAVIOR OF ADOLESCENTS IN PSYCHOLOGY PERSPECTIVE OF THE QUR'AN - Mela, Lita Mela; ichsan, ichsan (Psikoislamedia: Jurnal Psikologi, 2023)
Adolescents experience a transitional phase from childhood to early adolescents from middle adolescents must experience a transition to adulthood. In the transition phase, assertive behavior is very important for adolescents to have in expressing feelings and thinking of them as an effort to reduce the perpetrators of deviance and psychically strengthen the victims of adolescent deviance. The purpose of this study is to analyze the assertive behavior of adolescents in psychology as well as analyze the assertive behavior of adolescents from the perspective of the Qur'an. The technique used is a literature review by collecting several previous articles. The results of this study show that having Assertive behavior makes the individual understand himself, and his purpose in life, and assertive behavior make adolescents able to say right this is in line with the commands in Surah Al-Azhab verse 70 and Surah Al-Baqarah verse 42.  Able to reject and express his disapproval of the opinions of others, without offending them in line with QS. Ali Imran verse 159. Able to express pleasant and unpleasant feelings honestly in harmony with QS. An-Anfal verse 125.